Pengaruh Keaktifan Berorganisasi terhadap Perilaku Belajar Mahasiswa di Universitas Negeri Medan - Rachel Elisabet Ginting; Sani Susanti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of organizational involvement on students’ learning behavior at Universitas Negeri Medan. The research is motivated by the observation that student participation in campus organizations may have both positive and negative impacts on academic learning. A quantitative method with an ex post facto approach was employed. A total of 163 students were randomly selected from the population of active members across 12 Student Activity Units (UKM). Data were collected using a closed-ended questionnaire with a Likert scale. The results showed that students' level of organizational activity was generally high, with the majority classified under the